Pretrial procedure for settlement of contractual disputes in the context of general issues of legal activity in commercial organizations - A.N. Varlamova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper considers one of the most important legal means increasing the efficiency of activity in a commercial organization, i.e., pretrial procedure for settlement of contractual disputes, which is beyond the scope of legal regulation. Data on the evolution of its legal-regulatory framework in post-Soviet Russia have been provided. The regulatory potential and economic efficiency have been studied. The author is convinced that using pretrial procedure allows to settle disputes out of court and, thus, cut down costs of a commercial organization, as well as contributes to reducing tension without causing a complete termination of business relations. Practical problems of handling pretrial procedures in a company, its local and regulatory framework, and synchronization with claim and contractual activities of a corporate legal department have been discussed. It has been suggested to use a differentiated approach regarding the nature of the agreement and actual relations between the parties when constructing the contractual terms of pretrial procedure for dispute settlement. The article specifically covers the consequences of non-compliance with the pretrial procedure if such compliance is mandatory. It has been concluded that there is a direct relation between legal activity in a company and the sphere which is conditionally called legal management.